Analisis Pengaruh Green Marketing terhadap Loyalitas Pelanggan dengan Citra Merek sebagai Variabel Mediasi - Farah Meutia (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study aims to analyze the effect of green marketing on customer loyalty, with brand image as a mediating variable. In the context of increasing environmental awareness among consumers, green marketing strategies become an important element in building long-term relationships with customers. This study uses a quantitative approach with a survey method of 200 respondents who are active customers of green products. The data analysis technique uses structural equation modeling (SEM) based on Partial Least Squares (PLS). The results of the study indicate that green marketing has a significant positive effect on brand image, and brand image significantly mediates the effect of green marketing on customer loyalty. This means that companies that consistently implement green marketing strategies can build a strong brand image and ultimately increase consumer loyalty. The practical implications of this study suggest that companies should not only use green elements as a momentary marketing strategy, but integrate them into brand values ​​and operational activities as a whole. This study also encourages companies to improve communication about their environmental commitments through various digital marketing channels. Further studies are recommended to test this model in different industry sectors and consider variables such as consumer trust and corporate ethical values.